Laparoscopic Robotic Surgery in Gynecology - Hadisaputra, Wachyu (Indonesian Socety of Obstetrics and Gynecology, 2011)
Objective: To know the development and application of robot assisted laparoscopy in gynecology. Method: Literature review. Result: Laparoscopy procedure has been widely used since the last three decades where minimally invasive surgery cases and demands increase in urology, cardiac surgery, general surgery, and particularly, gynecology. To date, laparoscopy has developed into robot-assisted laparoscopy due to needs of precise dissection of delicate structures, procedures which requires sophisticated technique, and surgeonâs fatigue through the laparoscopy procedure. There are three robotic system which are commercialized and had been approved by FDA: AESOP, ZEUS, and Da Vinci, the latest robotic system which is used worldwide nowadays. There are advantages of robotic systems and conventional laparoscopy to open surgery laparotomy, such as diminished morbidity rate; less esthetical incisions; decreased post and intra operative blood loss, postoperative pain, use of pain medication, less cosmetic problems, and shorter length of hospital stay. Advantages of robotic surgery compared to conventional laparoscopy and laparotomy; include improved dexterity, more precise and accurate articulation, reduced tremor and surgeonâs fatigue, and better visualization of the operating field because of 3D image. Robotic system has drawbacks such as limited area of surgery field in trocar-placing to avoid collision of the robotic arms, longer operative time, and a higher cost. Conclusion: The major drawback of robot-assisted laparoscopy is in the term of cost; because of the high cost of robotic system; which could be overcome by a lower morbidity rate, less incisional aesthetic problem, less total intra operative blood loss, decreased demand of analgesics post operative, and shorter length of hospitalization stay and recovery time; as compensation of the high cost of robotic system. Further researches to study about the learning curve of robotic laparoscopy to achieve a faster operative time are needed. A longer operative time in robotic system can be anticipated with accurate simulation training in robotic system. There is also a need for further researches to discuss the total peri-operative cost. [Indones J Obstet Gynecol 2011; 35-3: 146-50] Keywords: laparoscopy, robotic system, robot-assisted, Da Vinci system, learning curve, gynecology